Pre-eclampsia/Eclampsia - Peraçoli, José Carlos; Borges, Vera Therezinha Medeiros; Ramos, José Geraldo Lopes; Cavalli, Ricardo de Carvalho; Costa, Sérgio Hofmeister de Almeida Martins; Oliveira, Leandro Gustavo de; Souza, Francisco Lazaro Pereira de; Korkes, Henri Augusto; Brum, Ione Rodrigues; Costa, Maria Laura; Corrêa Junior, Mário Dias; Sass, Nelson; Diniz, Angélica Lemos Debs; Prado, Caio Antonio de Campos; Cunha Filho, Edson Viera da (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Pre-eclampsia is a multifactorial and multisystemic disease specific to gestation. It is classically diagnosed by the presence of hypertension associated with proteinuria manifested in a previously normotensive pregnant woman after the 20th week of gestation. Pre-eclampsia is also considered in the absence of proteinuria if there is target organ damage. The present review takes a general approach focused on aspects of practical interest in the clinical and obstetric care of these women. Thus, it explores the still unknown etiology, current aspects of pathophysiology and of the diagnosis, the approach to disease prediction, its adverse outcomes and prevention. Management is based on general principles, on nonpharmacological and on pharmacological clinical treatment of severe or nonsevere situations with emphasis on the hypertensive crisis and eclampsia. Obstetric management is based on preeclampsia without or with signs of clinical and/or laboratory deterioration, stratification of gestational age in < 24 weeks, between 24 and less than 34 weeks, and ≥ 34 weeks of gestation, and guidance on route of delivery. An immediate puerperium approach and repercussions in the future life of pregnant women who develop preeclampsia is also presented.
Keywords: gestation; hypertensive disorders; pre-eclampsia; eclampsia